(untitled) (JOURNAL OF ADVANCES IN MATHEMATICS, 2021)
This work illustrates the intriguing relation between Metallic Means and the Numbers 3, 6 and 9. These numbers occupy special positions in the realm of Metallic Ratios, as elaborated herein.